2021
DOI: 10.3390/biology10080796
|View full text |Cite
|
Sign up to set email alerts
|

Possible Synergistic Antidiabetic Effects of Quantified Artemisia judaica Extract and Glyburide in Streptozotocin-Induced Diabetic Rats via Restoration of PPAR-α mRNA Expression

Abstract: Several members of the genus Artemisia are used in both Western and African traditional medicine for the control of diabetes. A considerable number of diabetic patients switch to using oral antidiabetic drugs in combination with certain herbs instead of using oral antidiabetic drugs alone. This study examined the effect of Artemisia judaica extract (AJE) on the antidiabetic activity of glyburide (GLB) in streptozotocin (STZ)-induced diabetes. Forty-two male Wistar rats were divided into seven equal groups. Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…This major anthropometric observation shifts the energy demand to fat and protein stores. Various studies have reported similar findings on the weight reduction in diabetic rats buttressing this study [ 51 53 ]. The modulation of weight loss by TCA may be ascribed to the improvement of glycaemic control.…”
Section: Discussionsupporting
confidence: 85%
“…This major anthropometric observation shifts the energy demand to fat and protein stores. Various studies have reported similar findings on the weight reduction in diabetic rats buttressing this study [ 51 53 ]. The modulation of weight loss by TCA may be ascribed to the improvement of glycaemic control.…”
Section: Discussionsupporting
confidence: 85%
“…Syringa vulgaris flower extract exhibited the presence of lilac alcohol stereoisomers C and D, which occupied >40% of the identified bioactive compounds [30]. Vulgarin is a sesquiterpene reported in Artemisia judaica possessing antihyperlipidemic and antihyperglycemic activities [31]. Halymeniad urvillei extract contains hexadecenoic acid [32].…”
Section: Resultsmentioning
confidence: 99%
“…Experimental diabetes was produced by a single dose of 45 mg/kg body weight of STZ (Merck& Co, Rahway, NJ, USA) in 0.01 M citrate buffer (pH 4.5) via intraperitoneal injection [7]. Diabetes was checked in blood samples collected from the tail veins of rats by measuring FBG levels using a blood glucose meter after three days (Accu-Check Performa, Roche Diagnostic, Germany).…”
Section: Induction Of Experimental Diabetesmentioning
confidence: 99%
“…In Jordan, the infusion of A. judaica is used by the Bedouins for the management of diabetes and sexual weakness [6]. The use of A. judaica extract with glibenclamide resulted in greater glycemic improvement than GLB monotherapy in male Wistar rats [7]. A detailed study traced the hypoglycemic effect of A. judaica to the eudesmanolid, vulgarin (VGN) (judaicin), and its isomer epivulgarin [8].…”
Section: Introductionmentioning
confidence: 99%